2019
DOI: 10.2478/bjmg-2019-0006
|View full text |Cite
|
Sign up to set email alerts
|

Duplication of the SOX3 gene in an sry-negative 46,XX male with associated congenital anomalies of kidneys and the urinary tract: Case report and review of the literature

Abstract: Disorders of sex development (DSD) are a group of rare conditions characterized by discrepancy between chromosomal sex, gonads and external genitalia. Congenital abnormalities of the kidney and urinary tract are often associated with DSD, mostly in multiple malformation syndromes. We describe the case of an 11-year-old Caucasian boy, with right kidney hypoplasia and hypospadias. Genome-wide copy number variation (CNV) analysis revealed a unique duplication of about 550 kb on chromosome Xq27, and a 46,XX karyot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
3
9
0
Order By: Relevance
“…About this deletion area, no similar report was found in the DGV database of the normal population, and no sexual reversal phenotype was reported in Decipher and ClinVar databases. Similar to previous reports [9,41], we speculated that the deletion region might involve the regulation region of the SOX3 gene, leading to differentiation and development of male testis through weakening inhibition of SOX3 and increasing expression SOX3 [9,42].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…About this deletion area, no similar report was found in the DGV database of the normal population, and no sexual reversal phenotype was reported in Decipher and ClinVar databases. Similar to previous reports [9,41], we speculated that the deletion region might involve the regulation region of the SOX3 gene, leading to differentiation and development of male testis through weakening inhibition of SOX3 and increasing expression SOX3 [9,42].…”
Section: Discussionsupporting
confidence: 84%
“…To date, 6 cases of SOX3 CNV related 46,XX male patients have been reported. In some cases, CNV duplication, including the SOX3 gene [39,41,42], resulted in the change of gene product dose. Some CNVS do not contain the SOX3 gene but are adjacent to the SOX3 gene region, or the breaking point of CNV falls in the regulatory region of SOX3, so it is speculated that CNV has a positional effect on SOX3 gene expression [9,43].…”
Section: Discussionmentioning
confidence: 99%
“…Among the analysed cases, the patient 3, a 12 years old boy with isolated GDD/ID, presents a 7.4 Mb duplication of X chromosome, including more OMIM genes, SOX3 being a known morbid gene, coding for a transcription factor implicated in neurogenesis, which is associated with mental retardation, X-linked, with isolated growth hormone de ciency. The patient presented a GDD/ID, same as other cases described in literature, but not short stature and GH de ciency (12,13,14,15). CNV was interpreted as pathogenic CNVs.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, XX sex reversal has been reported in transgenic mice with ectopic SOX3 expression and observed in 46, XX DSD patients with duplications of SOX3 or genomic rearrangements within the SOX3 regulatory region (16). Few reports are available on 46, XX SRY-negative males with SOX3 duplications, though a recent study conducted by Tasic et al revealed a 46, XX male who presented congenital anomalies of kidneys and the urinary tract and had a duplication on chromosome Xq27 involving the SOX3 gene, indicating links between SOX3 gene dosage and kidney malformations and sex determination (17). Moreover, a study has shown a 46, XX SRY-negative individual with duplication of the SOX3 gene exhibiting XX OT-DSD (18).…”
Section: Introductionmentioning
confidence: 99%